Chinese masculinity in Singapore and the multicultural marketplace in Kuo Pao Kun’s Descendants of the Eunuch Admiral - Sum, May-en (2016)
This paper discusses the allegorical interpretation of Kuo Pao Kun's Descendants of the Eunuch Admiral to shed light on Chinese masculinity in modern Singapore while also emphasising Kuo's ideal for multiculturalism in the capitalist marketplace. In doing so, I contend that Kuo's nuanced position towards multiculturalism is problematic but not necessarily impossible -- Multiculturalism will be argued to be the result of evolving cultural diversity in the dynamic marketplace, and it will be the cornerstone of the individual’s sense of identity and anchorage in this ever-changing capitalist world.